2015
DOI: 10.1039/c5ce00389j
|View full text |Cite
|
Sign up to set email alerts
|

Intracrystalline inclusions within single crystalline hosts: from biomineralization to bio-inspired crystal growth

Abstract: Many crystals in nature exhibit fascinating mechanical, optical, magnetic and other characteristics. One of the reasons for this phenomenon has to do with the presence of specific organic molecules that are tightly associated with the mineral. Over the years, some organic crystals have been found to be located within the lattices of their singlecrystalline biogenic hosts. A number of questions remain unanswered: for example, how do these molecules become incorporated and what is their function? In this review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 131 publications
(170 reference statements)
0
63
0
Order By: Relevance
“…Second, nonmineralization-related proteins present in endolymph (8,42) could have been trapped inside the developing otolith. Examples of organic macromolecule occlusion were previously shown for shells (43)(44)(45)(46), coccoliths (47), and sea urchin spines (48). Third, it should be noted that proteomics is very sensitive, and despite rigorous purification steps, the presence of some proteins may reflect contamination from other zebrafish tissues.…”
Section: Discussionmentioning
confidence: 93%
“…Second, nonmineralization-related proteins present in endolymph (8,42) could have been trapped inside the developing otolith. Examples of organic macromolecule occlusion were previously shown for shells (43)(44)(45)(46), coccoliths (47), and sea urchin spines (48). Third, it should be noted that proteomics is very sensitive, and despite rigorous purification steps, the presence of some proteins may reflect contamination from other zebrafish tissues.…”
Section: Discussionmentioning
confidence: 93%
“…[20]), is a "younger" and less studied subject, than inter-crystalline organics. [20]), is a "younger" and less studied subject, than inter-crystalline organics.…”
Section: Inter-crystalline and Intra-crystalline Organics In Bio-compmentioning
confidence: 99%
“…[50] Another important observation comes from laboratory experiments, in which calcite crystals are grown from solutions containing organic macromolecules. [20] The next question regards the specific mechanism standing behind the development of lattice distortions in biogenic calcium carbonate. [60,61] Calcite crystals, grown in the presence of purified caspartin at two different concentrations, 3 and 5 μg ml -1 , revealed expanded lattice parameters, which were found to increase with protein concentration up to Δc/c ≈ 0.1%.…”
Section: Physical Origin Of Anisotropic Lattice Distortionsmentioning
confidence: 99%
“…29 Organic molecules are attached to specific crystallographic planes and, hence, facilitate the formation of single crystals of different shapes (see e.g. brief review 30 ). For example, it was shown that proteins in P. lividus sea urchin spines are preferentially adsorbed on calcite planes parallel to the c-axis (hk0-planes), 23 whereas proteins from sponge spicules and from calcitic prims of mollusk shells are mostly attached to the (001)-planes.…”
Section: Introductionmentioning
confidence: 99%